HISCO
The Historical International Standard Classification of Occupations (HISCO) allows for all occupational titles in the world from the 18th to the 20th century to be ordered, connected and linked to short descriptions of activities of work. HISCO has a tree-like structure with 9 'major' groups, 76 'minor' groups, 296 'unit' groups and 1675 'micro' groups. The 'leaves' of the tree are formed by the ten-thousands of occupational titles that fall under these 1675 groups. Moving up or down the tree you can find related occupational groups. You may in addition find short definitions of the tasks and duties of an occupational group. HISCO also has subsidiary variables to capture additional information on social STATUS, on the PRODUCT used or on other matters, such as family of temporal reliationships.

radical online collections and archives (New Historical Express, 2018)
Keywords: _open access